2016
DOI: 10.1007/jhep03(2016)179
|View full text |Cite
|
Sign up to set email alerts
|

Blind spots for neutralino dark matter in the NMSSM

Abstract: Spin-independent cross-section for neutralino dark matter scattering off nuclei is investigated in the NMSSM. Several classes of blind spots for direct detection of singlinoHiggsino dark matter are analytically identified, including such that have no analog in the MSSM. It is shown that mixing of the Higgs doublets with the scalar singlet has a big impact on the position of blind spots in the parameter space. In particular, this mixing allows for more freedom in the sign assignment for the parameters entering … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 72 publications
0
84
0
Order By: Relevance
“…A quick look at Eq. (12) shows that such a large cross section is obtained for a high reheating temperature or small values of F (and thus a light gravitino), explaining the shape of the green region in Fig. 1.…”
Section: Gravitino Production Through Freeze-inmentioning
confidence: 76%
See 1 more Smart Citation
“…A quick look at Eq. (12) shows that such a large cross section is obtained for a high reheating temperature or small values of F (and thus a light gravitino), explaining the shape of the green region in Fig. 1.…”
Section: Gravitino Production Through Freeze-inmentioning
confidence: 76%
“…At the supersymmetric (SUSY) level, the authors of Ref. [12] showed that the well-tempered neutralino-which was the most robust supersymmetric candidate in recent years-is now severely constrained by the last results of LUX [6]. A wino-like neutralino is also severely constrained by the latest indirectdetection searches released by the Fermi Collaboration [3].…”
Section: Introductionmentioning
confidence: 99%
“…Still, such a mostly singlino-like LSP is good dark matter candidate [18] since its relic density can be reduced to the observed value via various processes like a mostly singletlike pseudoscalar in the s-channel, chargino exchange in the t-channel or co-annihilation. Furthermore a mostly singlino-like LSP can easily satisfy limits from direct and indirect dark matter detection experiments; its spin-independent direct detection cross section can even fall below the neutrino floor [19,20].…”
Section: Jhep02(2017)051mentioning
confidence: 99%
“…Another search channel is W H (where H is the Higgs boson of the Standard Model), where one assumes a χ 0 2 decay of the form χ 0 2 → H + χ 0 1 , still concentrating on the leptonic W ( * ) decay. Previous studies of constraints on, phenomenological aspects and future prospects of the light singlino scenario in the NMSSM have been performed in [15,20,. Here we proceed as follows: in the plane defined by the chargino (charged higgsino) mass M χ ± 1 < 300 GeV and the (mostly singlino-like) LSP mass…”
Section: Jhep02(2017)051mentioning
confidence: 99%
“…The compatibility with the LUX constraints is the reason for choosing negative value of M 1 in the benchmarks because µM 1 < 0 allows for some cancellations in the Higgs coupling to LSP which results in smaller SI scattering cross-section [70]. Additional suppression of the SI scattering cross-section may originate from destructive interference between the contributions to the SI scattering amplitude from the Higgs and the light singlet-scalar exchange which are of comparable size if Higgs-singlet mixing is non-negligible as in the present scenario [71]. For somewhat larger tan β SI scattering cross-section could be also suppressed by effects of destructive interference with the amplitude generated by MSSM-like Higgs exchange [72].…”
Section: Jhep02(2017)050mentioning
confidence: 82%